Searching for information sources: Students’ behaviour in electronic environment - Hebrang Grgić, Ivana (Array, 2012)
ICT is an important catalyst in transition from traditional to 21st century education. In the centre of our interests are students and their search for reliable information sources. The paper presents results of an online survey of all the students of Faculty of Humanities and Social Sciences, University of Zagreb (FHSS). Analysis will show how they search for information in electronic environment while preparing exams and writing theses. Students’ usage of library catalogue, commercial databases, open access repositories, open access journals, e-learning system, social networks, social bookmarking services, scientific blogs and forums will be analysed. Nine variables will be tested by chi-square test to show whether there are statistically significant differences in information searching behaviour between students of the Department of Information and Communication Sciences (DICS) and students of other departments at the faculty. All the results will show how important is formal education for using, evaluating and retrieving reliable information sources. The results will also accent some guidelines that will help educators and librarians at the faculty in planning education of their students/users.